Resilience In Christian Leadership: Building A Resilient Community - Dethan, Melly Putriyani; Kleden, Yakobus Beda; Octavianus, Philia; Soinbala, Nusriwan; Modok, Intan (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
Gereja Masehi Injili Di Timor (GMIT) Pengharapan Dendeng is one of the Christian Churches located in Kupang District, Central Kupang Classis, East Nusa Tenggara. In carrying out its ministry, GMIT Pengharapan Dendeng is under the auspices of the GMIT Synod. Advances in technology and social media have brought new challenges, such as issues of identity, social comparison, and digital addiction, which, if not managed properly, can become sources of stress. This has become a particular challenge for both the ministers and congregation of the Church, including the youth of GMIT Pengharapan Dendeng. In response to this situation, the Christian Leadership study program at IAKN Kupang organized a Community Service activity in the form of a workshop titled